Two decades after the arterial switch operation: stable right ventricular function but reduced exercise capacity - Renée S Joosen; Marielle C van de Veerdonk; Anneloes E Bohte; Tim Takken; Abraham van Wijk; Michael G Dickinson; Gregor J Krings; Michiel Voskuil; Johannes M.P.J. Breur (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Right ventricular (RV) function and exercise capacity predict prognosis in transposition of the great arteries (TGA) after arterial switch operation (ASO). We aim to longitudinally evaluate RV dimensions, global function and exercise capacity after ASO, comparing patients with and without RV pressure overload. Methods: This retrospective study included TGA patients post-ASO with two cardiovascular magnetic resonance (CMRs) examinations at the University Medical Center Utrecht between 2004 and March 2024. Cardiac volumes, function, strain, and vessel dimensions were measured. Patients were categorized by RV pressure overload. Repeated exercise tests were performed in a subset. The first and second CMR were compared. Results: The cohort (111 patients, 22±8years; 71% male (79/111)) underwent the first CMR at median 13 [11–19] years post-ASO (mid-term follow-up) and the second at 21 [16–26] years post-ASO (long-term follow-up). RV volumes, function, and strain remained stable during long-term follow-up. Aortic root dimensions showed no progression during long-term follow-up (diameter: 23±5 mm/m² vs. 20±4 mm/m², p<0.001). 50% (56/111) underwent exercise testing, revealing a VO2peak decline, with 25% (14/56) having reduced VO2peak at mid-term follow-up and 46% (26/56) at long-term follow-up (mean age 21±7years) (p=0.012). This was not related to peak heart rate or chronotropic index (peakHR: R=0.115, p=0.413; chronotropic index: R=0.099, p=0.484). No differences were observed between patients with and without RV pressure overload. Conclusion: Long-term exercise capacity is impaired in a significant portion of TGA patients. RV volumes, global function, strain, and aortic root dimensions remained unchanged during long-term follow-up post-ASO.